2018
DOI: 10.19184/jeam.v17i2.17334
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Rasio Keuangan terhadap Sustainability Perbankan di Indonesia: Menggunakan Regresi Logistik

Abstract: This study aims to look at the variables that affect financial sustainability. The data used are banking financial statement data contained in the FSS in 2013 to 2017. The value used to measure financial sustainability is FSS. The value of FSS as the dependent variable is divided into two categories, namely banks that are sustainable and banks that are not sustainable. Response variables used are financial ratios consisting of ROA, ROE, CTD, LTD, DTA, and CTA. The analysis used is logistic regression. Based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…The results of this study support the research results (Yuliawati et al, 2020), finding that ROA has no significant effect on the Financial Sustainability Ratio (FSR). However, in contrast to (Rianasari & Pangestuti, 2016;Miranti, 2018;Saputri, 2019) finding that Return On Assets (ROA) has a positive and significant effect on the Financial Sustainability Ratio (FSR).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The results of this study support the research results (Yuliawati et al, 2020), finding that ROA has no significant effect on the Financial Sustainability Ratio (FSR). However, in contrast to (Rianasari & Pangestuti, 2016;Miranti, 2018;Saputri, 2019) finding that Return On Assets (ROA) has a positive and significant effect on the Financial Sustainability Ratio (FSR).…”
Section: Discussionmentioning
confidence: 85%
“…The greater the Return On Assets (ROA) of a bank, the greater the level of profit achieved by the bank and the better the bank's position in terms of the use of its assets so that the bank can continue to be a going concern is in higher. The results of the study (Rianasari and Pangestuti, 2016;Miranti, 2018;Saputri, 2019) found that Return On Assets (ROA) had a positive and significant effect on the Financial Sustainability Ratio (FSR). Different results were found by (Yuliawati et al, 2020) found that ROA had no considerable impact on Financial Sustainability Ratio (FSR).…”
Section: Theoritical Reviewmentioning
confidence: 99%
“…Peranan perbankan yaitu sebagai salah satu penunjang perekonomian Indonesia mengharuskan perbankan untuk dapat terus sustain atau mengalami keberlanjutan keuangan (Miranti, 2018). Kemampuan berkelanjutan perusahaan pada Bank Umum Syariah dapat diukur dengan menggunakan rasio keberlanjutan keuangan atau Financial Sustainability Ratio (FSR).…”
Section: Pendahuluanunclassified
“…The results of the summary formation of the optimal classification tree indicate that the independent or independent variables that significantly influence the classification of banking FS are ROA, LTA, and DTA. It is reinforced by Khediri et al (2015), Choiruddin (2017), Miranti (2018) which states that ROA affects the economic viability of a company. The ROA variable appears to have a significant effect on financial sustainability.…”
Section: Figure 2 Maximum Tree Classificationmentioning
confidence: 99%